Super-wear-resistant high-temperature tungsten-based amorphous alloy and preparation method thereof

Through specific ratios of W, Fe, B, and C quadrimer alloys, ultra-wear-resistant high-temperature tungsten-based amorphous alloys without expensive metals were prepared, which solves the lack of wear resistance and high manufacturing cost of existing high-temperature amorphous alloys. The problem of high temperature thermal stability and wear resistance are improved, while reducing manufacturing costs.

CN119464972AActive Publication Date: 2025-02-18SOUTHWEST UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411612075.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing high-temperature amorphous alloys have insufficient wear resistance in high-temperature environments, and due to the existence of expensive metal elements, the manufacturing cost is high and it is difficult to widely use.

Method used

A quaternary alloy with specific ratios of W, Fe, B, and C were prepared by sputtering, ball milling, atomization, etc., and an ultra-wear-resistant high-temperature tungsten-based amorphous alloy without expensive metals was prepared.

Benefits of technology

High glass transition temperature and crystallization temperature are achieved, excellent high temperature thermal stability and ultra-high wear resistance, and reduce manufacturing costs, and can prepare bulk materials with a diameter of more than 1.5 mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464972A_ABST
    Figure CN119464972A_ABST
Patent Text Reader

Abstract

The invention discloses a super-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, the chemical formula of the super-wear-resistant high-temperature tungsten-based amorphous alloy is WaFebBcCd, a, b, c and d represent the atomic percentage content of corresponding chemical elements, a = 23-48, b = 32-57, c = 14-18, d = 2-6, a + b + c + d = 100, and the super-wear-resistant high-temperature tungsten-based amorphous alloy is composed of a single amorphous phase. The super-wear-resistant high-temperature tungsten-based amorphous alloy has the highest glass transition temperature of 840 DEG C and the crystallization temperature of about 900 DEG C, has good high-temperature stability and excellent amorphous forming ability, can obtain a block amorphous material with the three-dimensional size of 1.5-2 mm, has the wear resistance as low as 1.6 * 10 <-7 > mm < 3 > / Nm at room temperature, and can be used for preparing the high-temperature tungsten-based amorphous alloy. The high-temperature tungsten-based amorphous alloy can also be prepared into powder, films, wires or strips and other forms and combinations thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amorphous alloy materials, and specifically relates to an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof. Background Art

[0002] At present, metal materials are widely used in the fields of machinery manufacturing, aerospace, automobiles, ships, etc. However, during the service process, mechanical equipment will inevitably suffer from different degrees of wear and tear, causing equipment failure, which makes wear resistance an important criterion for determining its service life. Therefore, it is particularly important to research and develop metal materials with excellent wear resistance. Amorphous alloys, with their unique structure of long-range disorder and short-range order, often have better strength and hardness than traditional alloy materials, which means that amorphous alloys often have better wear resistance. However, since amorphous alloys are in a metastable state in energy, the instantaneous high temperature generated during the wear process will cause the amorphous alloy to crystallize locally, thereby greatly weakening its wear resistance. At present, the glass transition temperature of most amorphous alloys does not exceed 700°C, and the crystallization temperature does not exceed 800°C, which undoubtedly poses a huge challenge to long-term service in the high temperature stage (above 700°C). Therefore, the development of high-temperature amorphous alloy systems with higher glass transition temperatures has become an urgent problem to be solved in this field.

[0003] Existing studies have shown that refractory metals with high melting points and high modulus, such as Ir and Ta, are ideal materials for designing high-temperature amorphous alloys. The glass transition temperature of amorphous alloys designed with them as the main component can reach above 700°C. For example, Ming-Xing Li et al. (Nature, 2019, 569 99-103) reported that the IrNiTa (B) series of high-temperature amorphous alloys with glass transition temperatures above 800°C and crystallization temperatures above 900°C exhibited extremely excellent wear resistance (Adv. Sci. 2023, 2301053), but the manufacturing cost of the alloy is extremely high and difficult to apply in practice. Tungsten, as the metal material with the highest melting point, is much cheaper than Ir, Ta, etc. It is widely used in the manufacture of various high-temperature alloys and cemented carbides and has excellent wear resistance. Unfortunately, due to the extremely high melting point of tungsten, its crystallization driving force is high and its forming ability is limited. Currently, only the patent with application number CN116926447 A discloses a WCoTaB refractory bulk amorphous alloy, but the alloy still contains 5-10at.% of expensive metal Ta (~6000¥ / kg, 99.95wt.%, Beijing Cuibolin Nonferrous Metals Technology Development Center Co., Ltd., 2024.10). If a new tungsten-based amorphous alloy without any expensive metal and excellent amorphous forming ability can be prepared, it will be able to better meet the service conditions and further expand its application range.

[0004] In summary, in order to further improve the wear resistance of the alloy and better serve in high temperature extreme environments, it is very necessary to develop a tungsten-based amorphous alloy with excellent amorphous forming ability, high glass transition temperature and crystallization temperature, and ultra-high wear resistance. Summary of the invention

[0005] The object of the present invention is to provide a super wear-resistant high temperature tungsten-based amorphous alloy and a preparation method thereof, which can have excellent amorphous forming ability, high glass transition temperature and crystallization temperature and super high wear resistance, and does not contain expensive metal elements.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a super wear-resistant high temperature tungsten-based amorphous alloy, the chemical formula of the super wear-resistant high temperature tungsten-based amorphous alloy is: a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100, and the super wear-resistant high-temperature tungsten-based amorphous alloy is composed of a single amorphous phase.

[0008] Optionally, a=34-42, b=38-46, c=14-18, d=2-6, and a+b+c+d=100.

[0009] Optionally, the ultra-wear-resistant and high-temperature tungsten-based amorphous alloy may be in the form of any one of powder, film, wire, strip and block, or a combination of two or more thereof.

[0010] Optionally, the block diameter of the super wear-resistant high-temperature tungsten-based amorphous alloy is greater than 1.5 mm.

[0011] Optionally, the block diameter of the super wear-resistant high-temperature tungsten-based amorphous alloy is greater than 2 mm.

[0012] Optionally, the ultra-wear-resistant high-temperature tungsten-based amorphous alloy has a glass transition temperature of 780-840°C and a crystallization temperature of 820-900°C.

[0013] Optionally, the room temperature compressive strength of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is 5 to 6 GPa, the Young's modulus is 240 to 300 GPa, and the microhardness is 1500 to 1700 HV.

[0014] Optionally, the room temperature friction coefficient of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is 0.28-0.37, and the room temperature wear rate is 1.6×10 -7 ~1.2×10 -6mm 3 / Nm.

[0015] In a second aspect, the present invention provides a method for preparing the aforementioned ultra-wear-resistant high-temperature tungsten-based amorphous alloy, comprising at least one of sputtering, ball milling, atomization, belt spinning, suction casting or die casting.

[0016] Optionally, the following preparation steps are included:

[0017] S1. Weigh the raw materials according to the alloy composition: The chemical formula of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is: W a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100;

[0018] S2. Smelting raw materials to prepare master alloy ingots: The raw materials weighed in step S1 are uniformly melted in a vacuum or protective atmosphere to prepare master alloy ingots;

[0019] S3. Suction casting of the master alloy ingot into a water-cooled copper mold: The master alloy ingot prepared in step S2 is heated and smelted, and then suction cast into a water-cooled copper mold for cooling to prepare a high-temperature tungsten-based amorphous alloy.

[0020] In summary, the present invention has at least one of the following beneficial effects:

[0021] 1. The present invention provides an ultra-wear-resistant and high-temperature tungsten-based amorphous alloy. By adopting four specific elements, W, Fe, B and C, and a specific element ratio, a unique quaternary single-phase amorphous alloy is prepared. The glass transition temperature is 780-840°C, the crystallization temperature is 820-900°C, and it has excellent high-temperature thermal stability. In addition, the present invention uses low-cost tungsten among refractory metals as the main component element and does not contain precious metal elements, which effectively reduces the manufacturing cost. The prepared material has excellent amorphous forming ability and can prepare bulk materials with a diameter of 1.5 mm or even more than 2 mm. In addition, the good amorphous forming ability enables the amorphous alloy provided by the present invention to also prepare amorphous materials in the form of powders, films, wires or strips and their combinations.

[0022] 2. The present invention provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy, which has excellent comprehensive properties, including high strength, stiffness, hardness and excellent friction and wear properties. In the subsequent examples, it is measured that the room temperature compressive strength of the amorphous alloy can reach more than 5GPa, the Young's modulus can reach nearly 300GPa, and the microhardness can reach 1650HV. At room temperature, the friction coefficient is as low as 0.28, and the wear rate is as low as 1.6×10-7 mm 3 / Nm.

[0023] 3. The present invention provides a super wear-resistant high-temperature tungsten-based amorphous alloy, the chemical formula of which is: W a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100, a bulk amorphous with a diameter of more than 1.5 mm can be formed within a wider composition range, indicating that it has excellent amorphous forming ability within a wider composition range, and this series of alloys can provide a wide range of selection space and controllability for industrial applications; further, a=34-42, b=38-46, c=14-18, and d=2-6, a bulk amorphous with a diameter of more than 2 mm can be formed within a wider composition range, indicating that it has more excellent amorphous forming ability within this wider composition range. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD patterns of samples of Examples 1-5 of the present invention.

[0025] Figure 2 Neutron scattering diagrams of the samples of Examples 3 and 5 of the present invention.

[0026] Figure 3 1 and 2 are thermal analysis curves of the samples of Examples 3 and 5 of the present invention.

[0027] Figure 4 1 and 2 are stress-strain curves of the samples of Examples 3 and 5 of the present invention.

[0028] Figure 5 Nanoindentation load-displacement curves of the samples of Examples 3 and 5 of the present invention.

[0029] Figure 6 The microhardness diagram of the samples of Example 3 and Example 5 of the present invention.

[0030] Figure 7 Graph showing the coefficient of friction of Examples 3 and 5 of the present invention.

[0031] Figure 8 It is the wear curve diagram of Example 3 and Example 5 of the present invention. DETAILED DESCRIPTION

[0032] The present invention provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0033] The unique atomic arrangement of amorphous alloys, which is long-range disorder and short-range order, determines that amorphous alloys have a series of unique properties, such as good corrosion resistance, high strength, good wear resistance, etc., which provides a potential basis for amorphous alloys to be used as new structural materials in special fields. Generally speaking, amorphous alloys with higher glass transition temperature and crystallization temperature have better room temperature and high temperature mechanical properties, such as Ir-based and Ta-based. However, the high cost of raw materials greatly limits the actual engineering application scope of these high-stability amorphous alloys. The inventor disclosed a high-temperature W in the previously applied Chinese invention 202310886995.5. a Co b Ta c B d Amorphous alloy and preparation method thereof, the alloy has high glass transition temperature and crystallization temperature, its thermal stability can meet the high temperature (above 700°C) application, and has strong amorphous forming ability, and can obtain bulk material with three-dimensional size not less than 1 mm. However, it is still inevitable to add expensive metal element Ta. In order to break through the cost limit of expensive metal elements, the inventors, after a long period of research, surprisingly found that the quaternary alloy system of W, Fe, B, and C with a specific ratio has excellent amorphous forming ability and can obtain tungsten-based bulk amorphous materials with a critical size of more than 1.5 mm in diameter, or even up to 2 mm. In addition, the prepared specific tungsten-based amorphous material has a glass transition temperature of more than 700°C, even more than 780°C, and can reach up to 840°C. It has excellent high-temperature stability and can meet high-temperature (above 700°C) applications. The tungsten-based amorphous alloy has excellent wear resistance. The room temperature friction coefficient can reach below 0.5, even below 0.37, and the lowest can reach 0.28. The room temperature wear rate can reach 5×10 -6 mm 3 / Nm, even up to 1.2×10 -6 mm 3 / Nm, the minimum can reach 1.6×10 -7 mm 3 / Nm. It can be seen that the W, Fe, B, C quaternary alloy provided by the present invention can have excellent amorphous forming ability, high glass transition temperature and crystallization temperature and ultra-high wear resistance, and does not contain expensive metal elements. The present invention is obtained on the basis of this research.

[0034] Specifically, in some embodiments of the present invention, a super wear-resistant high temperature tungsten-based amorphous alloy is provided, and the chemical formula of the super wear-resistant high temperature tungsten-based amorphous alloy is: a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100, and the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is composed of a single amorphous phase; preferably, a=34-42, b=38-46, c=14-18, d=2-6, and a+b+c+d=100; more preferably, a=36-40, b=40-44, c=14-18, d=2-6, and a+b+c+d=100.

[0035] In some embodiments of the present invention, the form of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy includes any one or a combination of two or more of powder, film, wire, strip and block. The amorphous alloy in the form can be prepared by preparing a master alloy having the above-mentioned element composition ratio, and rapidly solidifying the molten liquid of the master alloy by rapid cooling. For example, a strip (wire) method can be used to spray the molten liquid of the master alloy onto a rotating copper roller to prepare a thin strip; a film can also be prepared by using a magnetron sputtering method; a powder can be prepared by a ball milling method or an atomization method; a block can be formed by a die casting method or a suction casting method.

[0036] In some embodiments of the present invention, the ultra-wear-resistant and high-temperature tungsten-based amorphous alloy is provided, and the diameter of the ultra-wear-resistant and high-temperature tungsten-based amorphous alloy is greater than 1.5 mm, preferably, the diameter is greater than 2 mm, preferably 2 mm.

[0037] In some embodiments of the present invention, a super wear-resistant high-temperature tungsten-based amorphous alloy is provided, wherein the glass transition temperature of the super wear-resistant high-temperature tungsten-based amorphous alloy is between 780 and 840°C, and the crystallization temperature is between 820 and 900°C.

[0038] In some embodiments of the present invention, a super wear-resistant high-temperature tungsten-based amorphous alloy is provided, and the room temperature compressive strength of the super wear-resistant high-temperature tungsten-based amorphous alloy is 5 to 6 GPa.

[0039] In some embodiments of the present invention, a super wear-resistant high temperature tungsten-based amorphous alloy is provided, and the Young's modulus of the super wear-resistant high temperature tungsten-based amorphous alloy is 240-300 GPa.

[0040] In some embodiments of the present invention, a super wear-resistant high-temperature tungsten-based amorphous alloy is provided, and the microhardness of the super wear-resistant high-temperature tungsten-based amorphous alloy is 1500-1700 HV.

[0041] In some embodiments of the present invention, the ultra-wear-resistant high-temperature tungsten-based amorphous alloy provided has a room temperature friction coefficient of 0.28 to 0.37 and a room temperature wear rate of 1.6×10 -7 ~1.2×10 -6 mm 3 / Nm.

[0042] The method for preparing the ultra-wear-resistant high-temperature tungsten-based amorphous alloy provided in some embodiments of the present invention comprises the following preparation steps:

[0043] S1. Weigh the raw materials according to the alloy composition: The chemical formula of the super wear-resistant tungsten-based amorphous alloy is: W a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100;

[0044] S2. Smelting raw materials to prepare master alloy ingots: The raw materials weighed in step S1 are uniformly melted in a vacuum or protective atmosphere to prepare master alloy ingots;

[0045] S3. Suction casting of the master alloy ingot into a water-cooled copper mold: The master alloy ingot prepared in step S2 is heated and smelted, and then suction cast into a water-cooled copper mold for cooling to prepare a high-temperature tungsten-based amorphous alloy.

[0046] The present invention is described in detail below in conjunction with specific embodiments.

[0047] Embodiment 1:

[0048] This embodiment provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, which specifically includes the following steps:

[0049] S1. Weigh the raw materials according to the alloy composition: the chemical formula of the alloy composition is W 23 Fe 57 B 16 C 4 , the components and atomic percentages of each component are as follows: W: 23%; Fe: 57%; B: 16%; C: 4%, the raw materials are single tungsten, iron, boron and carbon with a purity of not less than 99.9wt.%;

[0050] S2. Raw material smelting to prepare master alloy ingot: the raw material weighed in step S1 is placed in the first copper crucible of the arc melting furnace, and the sponge titanium is placed in the second copper crucible. The arc melting furnace is evacuated to 6×10 -3Pa, turn off the molecular pump, fill with argon to positive pressure, melt the titanium sponge in the second copper crucible to remove the residual impurity gas in the furnace, and then repeatedly melt the raw materials in the first copper crucible to obtain a master alloy ingot with uniform composition;

[0051] S3. Suction casting of mother alloy ingot into water-cooled copper mold: The mother alloy ingot prepared in step S2 is heated and melted, and then suction cast into a water-cooled copper mold with inner cavity diameters of 1.5 mm and 2 mm. After cooling, it is taken out to prepare 1.5 mm sample W1-1 and 2 mm sample W1-2.

[0052] The amorphous structure of the sample was characterized by XRD. Figure 1 As shown, only one diffuse peak was detected in the sample W1-1 of Example 1, and no sharp diffraction peak from the crystalline phase was detected, indicating that the 1.5 mm W1-1 sample prepared in Example 1 was a completely amorphous structure. After observing the W1-2 sample under a metallographic microscope, it was observed that a crystalline phase already existed in the W1-2 sample, indicating that the 2 mm W1-2 sample was an amorphous composite material.

[0053] Embodiment 2:

[0054] Embodiment 2 provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, which specifically comprises the following steps:

[0055] S1. Weigh the raw materials according to the alloy composition: the chemical formula of the alloy composition is W 36 Fe 44 B 16 C 4 , the components and atomic percentages of each component are as follows: W: 36%; Fe: 44%; B: 16%; C: 4%, the raw materials are single tungsten, iron, boron and carbon with a purity of not less than 99.9wt.%;

[0056] S2. Raw material smelting to prepare master alloy ingot: the raw material weighed in step S1 is placed in the first copper crucible of the arc melting furnace, and the sponge titanium is placed in the second copper crucible. The arc melting furnace is evacuated to 6×10 -3 Pa, turn off the molecular pump, fill with argon to positive pressure, melt the titanium sponge in the second copper crucible to remove the residual impurity gas in the furnace, and then repeatedly melt the raw materials in the first copper crucible to obtain a master alloy ingot with uniform composition;

[0057] S3. Suction casting of the master alloy ingot into a water-cooled copper mold: The master alloy ingot prepared in step S2 is heated and smelted, and then suction-cast into a water-cooled copper mold with an inner cavity diameter of 2 mm. After cooling, it is taken out to prepare sample W2.

[0058] The amorphous structure of the sample was characterized by XRD. Figure 1As shown, only one diffuse peak was detected for sample W2 of Example 2, and no sharp diffraction peak from the crystalline phase was detected, indicating that the 2 mm W2 sample prepared in Example 2 was a completely amorphous structure.

[0059] Embodiment 3:

[0060] Embodiment 3 provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, which specifically comprises the following steps:

[0061] S1. Weigh the raw materials according to the alloy composition: the chemical formula of the alloy composition is W 40 Fe 40 B 16 C 4 , the components and atomic percentages of each component are as follows: W: 40%; Fe: 40%; B: 16%; C: 4%, the raw materials are single tungsten, iron, boron and carbon with a purity of not less than 99.9wt.%;

[0062] S2. Raw material smelting to prepare master alloy ingot: the raw material weighed in step S1 is placed in the first copper crucible of the arc melting furnace, and the sponge titanium is placed in the second copper crucible. The arc melting furnace is evacuated to 6×10 -3 Pa, turn off the molecular pump, fill with argon to positive pressure, melt the titanium sponge in the second copper crucible to remove the residual impurity gas in the furnace, and then repeatedly melt the raw materials in the first copper crucible to obtain a master alloy ingot with uniform composition;

[0063] S3. Suction casting of the master alloy ingot into a water-cooled copper mold: The master alloy ingot prepared in step S2 is heated and smelted, and then suction cast into a water-cooled copper mold with an inner cavity diameter of 2 mm. After cooling, it is taken out to prepare sample W3.

[0064] The amorphous structure of the sample was characterized by XRD. Figure 1 As shown, only one diffuse peak was detected for sample W3 of Example 3, and no sharp diffraction peak from the crystalline phase was detected, indicating that the 2 mm W3 sample prepared in Example 3 was a completely amorphous structure.

[0065] Neutron scattering technology was used to characterize the amorphous structure of the sample. The neutron scattering spectrum of the sample W3 prepared in Example 3 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the spectrum of sample W3 is a smooth curve, and no crystalline phase is detected at the nanoscale, indicating that the 2 mm sample prepared in Example 3 is a completely amorphous structure.

[0066] The thermal stability of the samples was investigated using a differential thermal analyzer with a heating rate of 20 °C / min. Figure 3As shown, the glass transition temperature of sample W3 of Example 3 was measured to be 788° C., and the crystallization temperature was 820° C., indicating that sample W3 has good high temperature stability.

[0067] The room temperature compressive strength of the sample was tested by a universal mechanical testing machine. Figure 4 As shown, the room temperature compressive strength of sample W3 of Example 3 was measured to be 5.1 GPa.

[0068] The Young's modulus of the samples was studied by nanoindentation. Figure 5 As shown, after calculation, the Young's modulus of the sample W3 of Example 3 is 240 GPa.

[0069] The microhardness of the sample was studied by microhardness tester, such as Figure 6 As shown, the microhardness of sample W3 of Example 3 is 1595±17 HV.

[0070] The wear resistance of the samples was tested by friction and wear tester. Figure 7 As shown, the friction coefficient of sample W3 of Example 3 is 0.28.

[0071] The wear rate of the samples was calculated by profilometer, as Figure 8 As shown in the figure, the wear rate of sample W3 in Example 3 is 1.6×10 -7 mm 3 / Nm.

[0072] Embodiment 4:

[0073] Embodiment 4 provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, which specifically comprises the following steps:

[0074] S1. Weigh the raw materials according to the alloy composition: the chemical formula of the alloy composition is W 44 Fe 36 B 16 C 4 , the components and atomic percentages of each component are as follows: W: 44%; Fe: 36%; B: 16%; C: 4%, the raw materials are single tungsten, iron, boron and carbon with a purity of not less than 99.9wt.%;

[0075] S2. Raw material smelting to prepare master alloy ingot: the raw material weighed in step S1 is placed in the first copper crucible of the arc melting furnace, and the sponge titanium is placed in the second copper crucible. The arc melting furnace is evacuated to 6×10 -3 Pa, turn off the molecular pump, fill with argon to positive pressure, melt the titanium sponge in the second copper crucible to remove the residual impurity gas in the furnace, and then repeatedly melt the raw materials in the first copper crucible to obtain a master alloy ingot with uniform composition;

[0076] S3. Suction casting of mother alloy ingot into water-cooled copper mold: The mother alloy ingot prepared in step S2 is heated and melted, and then suction cast into a water-cooled copper mold with inner cavity diameters of 1.5 mm and 2 mm. After cooling, it is taken out to prepare 1.5 mm sample W4-1 and 2 mm sample W4-2.

[0077] The amorphous structure of the sample was characterized by the same test method as in Example 1. Figure 1 As shown, the diffraction peak of sample W4-1 in Example 4 only detected a diffuse peak, and no sharp diffraction peak from the crystal phase was detected, indicating that sample W4-1 is a completely amorphous structure. Observation under a metallographic microscope showed that sample W4-2 had a partial crystalline phase, indicating that the 2 mm sample W4-2 was an amorphous composite material.

[0078] Embodiment 5:

[0079] Embodiment 5 provides an ultra-wear-resistant high-temperature tungsten-based amorphous alloy and a preparation method thereof, which specifically comprises the following steps:

[0080] S1. Weigh the raw materials according to the alloy composition: the chemical formula of the alloy composition is W 48 Fe 32 B 16 C 4 , the components and atomic percentages of each component are as follows: W: 48%; Fe: 32%; B: 16%; C: 4%, the raw materials are single tungsten, iron, boron and carbon with a purity of not less than 99.9wt.%;

[0081] S2. Raw material smelting to prepare master alloy ingot: the raw material weighed in step S1 is placed in the first copper crucible of the arc melting furnace, and the sponge titanium is placed in the second copper crucible. The arc melting furnace is evacuated to 6×10 -3 Pa, turn off the molecular pump, fill with argon to positive pressure, melt the titanium sponge in the second copper crucible to remove the residual impurity gas in the furnace, and then repeatedly melt the raw materials in the first copper crucible to obtain a master alloy ingot with uniform composition;

[0082] S3. Suction casting of mother alloy ingot into water-cooled copper mold: The mother alloy ingot prepared in step S2 is heated and melted, and then suction cast into a water-cooled copper mold with inner cavity diameters of 1.5 mm and 2 mm. After cooling, it is taken out to prepare 1.5 mm sample W5-1 and 2 mm sample W5-2.

[0083] The amorphous structure of the sample was characterized by an X-ray diffractometer. The XRD pattern of the sample W5-1 prepared in Example 5 is as follows: Figure 1 As shown, from Figure 1It can be seen that only one diffuse peak was detected in the diffraction peak of sample W5-1, and no sharp diffraction peak from the crystal phase was detected, indicating that the 1.5 mm sample W5-1 prepared in Example 5 is a completely amorphous structure. The W5-2 sample was observed under a metallographic microscope to have a partial crystalline phase, indicating that the 2 mm W5-2 sample is an amorphous composite material.

[0084] Neutron scattering technology was used to characterize the amorphous structure of the sample. The neutron scattering spectrum of the sample W5-1 prepared in Example 5 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the spectrum of sample W5-1 is a smooth curve, and no crystalline phase is detected at the nanoscale, indicating that the 1.5 mm sample W5-1 prepared in Example 5 is a completely amorphous structure.

[0085] The thermal stability of the samples was investigated using a differential thermal analyzer with a heating rate of 20 °C / min. Figure 3 As shown, the glass transition temperature of sample W5-1 of Example 5 was measured to be 840°C, and the crystallization temperature was 894°C, indicating that sample W5-1 has good high temperature stability.

[0086] The room temperature compressive strength of the sample was tested by a universal mechanical testing machine. Figure 4 As shown, the room temperature compressive strength of sample W5-1 of Example 5 is 5.6 GPa.

[0087] The Young's modulus of the samples was studied by nanoindentation. Figure 5 As shown, after calculation, the Young's modulus of the sample W5-1 of Example 5 is 296 GPa.

[0088] The microhardness of the sample was studied by microhardness tester, such as Figure 6 As shown, the microhardness of sample W5-1 of Example 5 is 1650±20 HV.

[0089] The wear resistance of the samples was tested by friction and wear tester. Figure 7 As shown, the friction coefficient of sample W5-1 in Example 5 is 0.37.

[0090] The wear rate of the samples was calculated by profilometer, as Figure 8 As shown, the wear rate of sample W5-1 in Example 5 is 1.2×10 -6 mm 3 / Nm.

[0091] The amorphous samples of Examples 1, 2 and 4 were tested using the same testing method as that of Examples 3 and 5, and it was found that the amorphous samples of Examples 1, 2 and 4 also had excellent comprehensive properties.

[0092] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A super wear-resistant high temperature tungsten-based amorphous alloy, characterized in that: The chemical formula of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is: a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100, and the super wear-resistant high-temperature tungsten-based amorphous alloy is composed of a single amorphous phase.

2. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1, characterized in that: a=34~42, b=38~46, c=14~18, d=2~6, and a+b+c+d=100.

3. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1 or 2, characterized in that: The ultra-wear-resistant high-temperature tungsten-based amorphous alloy may be in the form of any one of powder, film, wire, strip and block, or a combination of two or more thereof.

4. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1 or 2, characterized in that: The block diameter of the super wear-resistant high-temperature tungsten-based amorphous alloy is greater than 1.5 mm.

5. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 4, characterized in that: The block diameter of the super wear-resistant high-temperature tungsten-based amorphous alloy is greater than 2 mm.

6. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1 or 2, characterized in that: The ultra-wear-resistant high-temperature tungsten-based amorphous alloy has a glass transition temperature of 780-840°C and a crystallization temperature of 820-900°C.

7. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1 or 2, characterized in that: The room temperature compressive strength of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is 5-6 GPa, the Young's modulus is 240-300 GPa, and the microhardness is 1500-1700 HV.

8. The ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 1 or 2, characterized in that: The room temperature friction coefficient of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is 0.28-0.37, and the room temperature wear rate is 1.6×10 -7 ~1.2×10 -6 mm 3 / Nm.

9. A method for preparing the ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to any one of claims 1 to 8, characterized in that: The method comprises at least one of sputtering, ball milling, atomization, belt spinning, suction casting or die casting.

10. The method for preparing the ultra-wear-resistant high-temperature tungsten-based amorphous alloy according to claim 9, characterized in that: The method comprises the following preparation steps: S1. Weigh the raw materials according to the alloy composition: The chemical formula of the ultra-wear-resistant high-temperature tungsten-based amorphous alloy is: W a Fe b B c C d , wherein a, b, c, and d represent the atomic percentage content of the corresponding chemical elements, a=23-48, b=32-57, c=14-18, d=2-6, and a+b+c+d=100; S2. Smelting raw materials to prepare master alloy ingots: The raw materials weighed in step S1 are uniformly melted in a vacuum or protective atmosphere to prepare master alloy ingots; S3. Suction casting of the master alloy ingot into a water-cooled copper mold: The master alloy ingot prepared in step S2 is heated and smelted, and then suction cast into a water-cooled copper mold for cooling to prepare a high-temperature tungsten-based amorphous alloy.

Citation Information

Patent Citations

  • Tungsten based amorphous alloy

    CN101353771A

  • Tungsten-based high-temperature block amorphous alloy and preparation method thereof

    CN116926447A

  • High strength amorphous alloy and its production

    JP2000265252A

  • Metallic glasses with high crystallization temperatures and high hardness values

    US4059441A

  • Method of blow molding a bulk metallic glass

    WO2009070701A1